How to achieve sustainable buyer–seller relationship in social commerce? The effect of network closure on ties evolution - Zhang, Hao; Han, Xiao; Zheng, Shiyong; Gu, Mohan (Frontiers in Psychology, 2023)
The fact that most buyer-seller ties in the social commerce community are easy to form but hard to keep has brought the "social bubble" into social commerce. Following the literature streams of network closure and social commerce and based on the longitudinal dataset of an online social commerce community over a year, this article explores the buyer-seller ties evolution in the social commerce community through two stages, that is, ties emergence versus ties persistence. Our results show an asymmetric effect of network closure mechanisms across different stages of buyer-seller ties evolution. In the early stage of buyer-seller ties, due to the information asymmetry, buyers usually rely on informative signals that either reflect the "popular others" (i.e., the popularity and content sharing) or the "ideal self" (i.e., the value homophily and status homophily) to form ties with sellers, which makes the community more "transactional." As very few ties can survive through the periods of 3 months or more, the normative social influence, which relies heavily on the structure of extant relationships among community members, becomes the dominant driver of ties persistence, which makes the community more "social." This study contributes to the ongoing research of network analysis and social commerce. It provides valuable tactics to sellers who want to develop long-term relationships with buyers in the social commerce community.